Socioeconomic determinants of respiratory health in patients with cystic fibrosis: implications for treatment strategies. Issue 6 (3rd June 2022) - Oates, Gabriela R.; Schechter, Michael S.
ABSTRACT: Introduction: Great variation exists in the progression and outcomes of cystic fibrosis (CF) lung disease, due to both genetic and environmental influences. Social determinants mediate environmental exposures and treatment success; people with CF from socioeconomically disadvantaged backgrounds have worse health and die younger than those in more advantaged positions. Areas covered: This paper reviews the literature on the mechanisms that are responsible for generating and sustaining disparities in CF health, and the ways by which social determinants translate into health advantages or disadvantages in people with CF. The authors make recommendations for addressing social risk factors in CF clinical practice. Expert opinion: Socioeconomic factors are not dichotomous and their impact is felt at every step of the social ladder. CF care programs need to adopt a systematic protocol to screen for health-related social risk factors, and then connect patients to available resources to meet individual needs. Considerations such as daycare, schooling options, living and working conditions, and opportunities for physical exercise and recreation as well as promotion of self-efficacy are often overlooked. In addition, advocacy for changes in public policies on health insurance, environmental regulations, social welfare, and education would all help address the root causes of CF health inequities.